2011
DOI: 10.3390/s110706603
|View full text |Cite
|
Sign up to set email alerts
|

Remote Real-Time Monitoring of Subsurface Landfill Gas Migration

Abstract: The cost of monitoring greenhouse gas emissions from landfill sites is of major concern for regulatory authorities. The current monitoring procedure is recognised as labour intensive, requiring agency inspectors to physically travel to perimeter borehole wells in rough terrain and manually measure gas concentration levels with expensive hand-held instrumentation. In this article we present a cost-effective and efficient system for remotely monitoring landfill subsurface migration of methane and carbon dioxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…A previous work [15] showed that three operations are carried out for methane measurement in a landfill: baseline, sampling and purge. The first introduces atmospheric air to the chamber, the second measures methane and the purge, sucks the sampled gas away.…”
Section: Resultsmentioning
confidence: 99%
“…A previous work [15] showed that three operations are carried out for methane measurement in a landfill: baseline, sampling and purge. The first introduces atmospheric air to the chamber, the second measures methane and the purge, sucks the sampled gas away.…”
Section: Resultsmentioning
confidence: 99%
“…This was ideally suited for environmental systems as, in most cases, such devices are deployed in remote locations without access to local hot spots (e.g., WiFi or locally placed base stations). Furthermore, the infrastructure allowed for many sensing nodes (i.e., scope), and the data were sent via SMS, which required a quick energy burst for reduction of energy; see [ 65 ] for more details. For the home energy monitoring, the data were transmitted via Zigbee-based protocol to a local receiver (base station), and the household’s Internet connection was used for data delivery.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, this technique is not yet suitable for applications, where it is necessary to resolve lower CO 2 concentrations, e.g., for air-quality monitoring [54]. However, there might be other use cases such as human breath analysis [10] or landfill gas monitoring [11]. In the case of H 2 , we can use our own study as a benchmark.…”
Section: Sensitivitymentioning
confidence: 99%
“…On the other hand, these sensors exhibit a measurement range limited to a few percent [2] which also applies to catalytic [7] and work function-based sensors [8,9]. For certain applications, such as human breath analysis [10], or landfill gas monitoring [11], however, a large measurement range is more important than an ultra-low resolution limit. Optical [12][13][14] and mechanical [15,16] sensors do have a large measurement range but at the expense of a slow response time.…”
Section: Introductionmentioning
confidence: 99%